Corrections to “Older Users Acceptance of Smart Products: An Extension of the Technology Acceptance Model” - Hui Zeng; Jinwei Zhu; Hanxi Lin; Junming Chen (IEEE Access)
Presents corrections to the paper, (Corrections to “Older Users Acceptance of Smart Products: An Extension of the Technology Acceptance Model”).